Growth and characterization of BaZnGa. Issue 35 (12th December 2017) - Jo, Na Hyun; Lin, Qisheng; Nguyen, Manh Cuong; Kaluarachchi, Udhara S.; Meier, William R.; Manni, Soham; Downing, Savannah S.; Böhmer, Anna E.; Kong, Tai; Sun, Yang; Taufour, Valentin; Wang, Cai-Zhuang; et al.
Abstract: We report the growth, structure and characterization of BaZnGa, identifying it as the sole known ternary compound in the Ba–Zn–Ga system. Single crystals of BaZnGa can be grown out of excess Ba–Zn and adopt a tI36 structure type. There are three unique Ba sites and three M = Zn/Ga sites. Using DFT calculations we can argue that whereas one of these three M sites is probably solely occupied by Ga, the other two M sites, most likely, have mixed Zn/Ga occupancy. Temperature-dependent resistivity and magnetization measurements suggest that BaZnGa is a poor metal with no electronic or magnetic phase transitions between 1.8 and 300 K.